2001
DOI: 10.1086/319119
|View full text |Cite
|
Sign up to set email alerts
|

Detection of [N [CSC]ii[/CSC]] λ5755 Emission from Low-Density Ionized Interstellar Gas

Abstract: The extremely faint, temperature-sensitive "auroral" emission line [N ii] l5755 has been detected from the low-density ionized gas along the sight line toward , using the Wisconsin Ha Mapper. The l p 130Њ .0 b p Ϫ7Њ .5 intensity of this emission line, relative to the red nebular line [N ii] l6584, is found to be twice that observed in bright, classical H ii regions surrounding O stars. This implies that the electron temperature of the ionized gas along this sight line is about 2000 K higher than the H ii regio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Models of N + in the WIM at T K = 8000 K reproduce both the submm-wave absorption towards W 49N and W 31C reported here and the intensities of [N ii] 6583, 5755, and Hα 6563 Å reported by Reynolds et al (2001). The latter refer to emission lines over a one-degree region in the direction G130.0 − 7.5 in several broad velocity components with corresponding kinematical distances between 0.6 kpc and 9.7 kpc.…”
Section: Radex Modellingsupporting
confidence: 71%
See 1 more Smart Citation
“…Models of N + in the WIM at T K = 8000 K reproduce both the submm-wave absorption towards W 49N and W 31C reported here and the intensities of [N ii] 6583, 5755, and Hα 6563 Å reported by Reynolds et al (2001). The latter refer to emission lines over a one-degree region in the direction G130.0 − 7.5 in several broad velocity components with corresponding kinematical distances between 0.6 kpc and 9.7 kpc.…”
Section: Radex Modellingsupporting
confidence: 71%
“…The same conditions explain the diffuse optical emission lines of [N ii] and Hα (Reynolds et al 2001). The real interstellar medium is, however, more complex than our static, uniform models; in particular, the WIM represents an average over space and time of wildly varying conditions (Dong & Draine 2011).…”
Section: Radex Modellingmentioning
confidence: 54%
“…The last six rows show the data obtained for sight lines that sample the much fainter diffuse ionized medium. One WIM sight line, (130 , À7N5), was reported previously by Reynolds et al (2001b). For some directions, [N ii] k5755 was not detected, and only upper limits to the line ratio of [N ii] k5755/[N ii] k6584 are given, as described in x 3.3.…”
Section: Observations Of [N Ii] K5755mentioning
confidence: 84%
“…In addition, the elevated [N ii]/ H and [S ii]/ H ratios in the WIM suggest that this low-density diffuse gas is significantly warmer than traditional H ii regions and may require spectral processing of the stellar radiation (e.g., Wood & Mathis 2004) and /or an additional heating source beyond photoionization ). Recent observations of [ N ii] k5755/ [N ii] k6583 have indeed confirmed that the WIM is about 2000 K warmer than H ii regions (Reynolds et al 2001b). …”
mentioning
confidence: 86%
See 1 more Smart Citation